Phenotypic differentiation in populations of a gladiator tree frog: environment, genetic drift and sexual selection - Nali, Renato C [UNESP]; Zamudio, Kelly R; Prado, Cynthia P. A [UNESP] (Oxford University Press (OUP), 2023)
Phenotypic differentiation among animal populations is common, yet few studies have simultaneously examined the adaptive and neutral mechanisms behind it. Such evolutionary processes become more relevant in species with complex behaviours that undergo global and local selective pressures throughout their geographical range. Here we measured and compared morphological and acoustic variation across the distribution range of a Neotropical gladiator tree frog that shows elaborate reproduction (territoriality, complex courtship and female choice). We then incorporated molecular and landscape data to examine the roles of sexual selection, genetic drift and acoustic adaptation to the environment in call differentiation, i.e. the acoustic adaptation hypothesis (AAH). We found that calls varied more than morphology among populations, but differences in calls or morphological traits were not explained by genetic differentiation. We found no evidence for the AAH, but a significant relationship in the opposite direction regarding call frequencies suggests an indirect role of sexual selection. Differentiation on call traits that are associated with individual discrimination and/or female attraction also corroborated an important role of sexual selection. We show that multitrait and multimechanism approaches can elucidate intricate processes leading to phenotypic variation among individuals and populations. We emphasize that studies of species with complex reproductive behaviours across their range may provide insights into different selective pressures leading to phenotypic differentiation.
Keywords: Amphibia; bioacoustics; Bokermannohyla ibitiguara; Brazil; complex vocalization; genetic differentiation; Hylidae; intraspecific variation; morphometry